2019
DOI: 10.4049/jimmunol.1900572
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Mucosal NKp44+ Innate Lymphoid Cells and Δγ Cells on Simian Immunodeficiency Virus Infection Outcome in Rhesus Macaques

Abstract: NK cells are essential for controlling viral infections. We investigated NK cell and innate lymphoid cell (ILC) dynamics and function in rhesus macaque rectal tissue and blood following mucosal priming with replicating adenovirus (Ad)-SIV recombinants, systemic boosting with SIV envelope protein, and subsequent repeated low-dose intravaginal SIV exposures. Mucosal memory-like NK and ILC subsets in rectal and vaginal tissues of chronically infected macaques were also evaluated. No differences in NK cell or ILC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…(38). Thus, to determine if the E4 genes had any impact on this ability we performed ADCC as summarized in the method section and described elsewhere (52). Here, even though the ADCC values from the ΔE4 Ad-immunized NHPs were higher than those of the other Ad-immunized NHPs, no significant differences were observed either against gp120 or rhFLSC targets ( Fig 5C).…”
Section: Ad Early Genes Modulate Levels Of Transgene-specific Antibodmentioning
confidence: 93%
See 1 more Smart Citation
“…(38). Thus, to determine if the E4 genes had any impact on this ability we performed ADCC as summarized in the method section and described elsewhere (52). Here, even though the ADCC values from the ΔE4 Ad-immunized NHPs were higher than those of the other Ad-immunized NHPs, no significant differences were observed either against gp120 or rhFLSC targets ( Fig 5C).…”
Section: Ad Early Genes Modulate Levels Of Transgene-specific Antibodmentioning
confidence: 93%
“…ADCC activity was assessed as previously described using EGFP-CEMNKr-CCR5-SNAP cells that constitutively express GFP as targets (52). Briefly, one million target cells were incubated with 50 μg of BAL gp120 or rhFLSC recombinant protein for 2 h at 37ºC, washed, and labeled with SNAP-Surface Alexa Fluor 647 (New England Biolabs, Ipswich, MA; cat.# S9136S) as on March 21, 2021 by guest http://jvi.asm.org/ Downloaded from recommended by the manufacturer for 30 min at RT.…”
Section: Antibody Analysesmentioning
confidence: 99%
“…Helper ILCs are classified into ILC1, ILC2, and ILC3, based on expression of major transcription factors and their signature cytokines, which resemble those of Th1, Th2 and Th17/Th22 cell subsets. In general, ILC1 produces IFN-γ; ILC2 produces IL-4, IL-5 and IL-13; and ILC3 produces IL-17A and/or IL-22 ( 32 , 33 , 36 , 37 ). Recent evidence also showed the plasticity of ILCs that enable them to promptly respond to environmental changes ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned study corroborated the premise that the lentivirus infection could have significant effects on the frequency, phenotype, and function of innate cells in the oral and gut mucosa such as the reduction of ILC3 IL-22 + which might be particularly relevant in infants infected through breastfeeding, because their immune system is not fully functional (62). Importantly, it has recently been demonstrated that NKp44 + ILCs play a protective role in the progression of the disease, as their higher frequency in the mucosa was associated with delayed SIV acquisition and decreased viremia in vaccinated macaques (63), thus confirming previous published data (64).…”
Section: The Repercussion Of Blood or Systemic Infections In Ilc3 Population Immunodeficiency Viruses Reduce Ilc3s In Infected Subjectsmentioning
confidence: 99%